On creditor seniority and sovereign bond prices in Europe - Sven Steinkamp; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2012)
The recent increase of interest rate spreads in Europe and their apparent detachment from underlying fundamental variables has generated a debate on multiple equilibria in the sovereign bond market (see De Grauwe and Ji (2012)). We critically evaluate this hypothesis, by pointing towards an alternative explanation: the increasing share of senior lenders (IMF, ECB, EFSF, etc.) in the total outstanding government debt of countries in crisis. We illustrate the close relationship between senior tranche lending - including Target2 balances - and recent developments in the sovereign bond market, both graphically and in a formal regression analysis.
Keywords: F34; G12; H81; 330; government bond spreads; Eurozone; senior tranche lending; multiple equilibria; sovereign debt crisis; Target2; Öffentliche Anleihe; Börsenkurs; Öffentliche Schulden; Zinsstruktur; Internationaler Kredit; Internationaler Zahlungsverkehr; Zahlungsbilanzungleichgewicht; Gleichgewicht; Eurozone